Redefinisi Frasa Kepentingan Umum Atas Pengelolaan Tanah Masyarakat Adat Berdasar-kan Pendekatan Konsep Welfare State (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
Indonesia as a developing country requires maximum infrastructure development for the public interest or in other words for the realization of people's welfare. Indigenous peoples' land which is used as the object of infrastructure development without prior approval can result in violation of the rights of indigenous peoples. By using a normative juridical method, this research focuses on reviewing the approval of indigenous peoples whose land is the object of infrastructure development in the public interest. This then becomes important because to what extent is the definition of public interest formulated in the phrase the interests of the State and common interests often lead to prolonged conflicts. The redefinition of public interest by using the concept of the welfare state approach is then deemed relevant for the creation of a responsive land law politics. Keywords: culture; development infrastructure; public interest Abstrak Indonesia sebagai negara berkembang memerlukan pembangunan infrastruktur yang maksimal demi kepentingan umum atau dengan kata lain demi mewujudkan kesejaheraan rakyat. Tanah masyarakat adat yang dijadikan objek pembangunan infrastruktur tanpa adanya persetujuan terlebih dahulu dapat menimbulkan pencideraan hak masyarakat adat. Dengan menggunakan metode yuridis normatif, peneltian ini fokus mengkaji terkait persetujuan dari masyarakat hukum adat yang tanahnya dijadikan objek dalam pembangunan infrastruktur demi kepentingan umum. Hal ini kemudian menjadi penting karena sejauh apa definisi kepentingan umum yang dirumuskan dalam frasa kepentingan Negara dan kepentingan bersama itu sering kali meimbulkan konflik berkepanjangan. Redefinisi kepentingan umum dengan menggunakan pendekatan konsep welfare state kemudian dianggap relevan untuk tercipata politik hukum pertanahan yang responsif. Kata kunci: kepentingan umum; masyarakat adat; pembangunan infrastruktur